Questions of the brothers - Basil, Saint, Bishop of Caesarea, approximately 329-379 (Texts and studies in Eastern Christianity., 2014)
Questions of the Brothers, the Syriac translation of Basil of Caesarea's Small Asketikon, is edited for the first time from ancient manuscripts and translated into English. Silvas highlights the unique character of the Syriac translator's own contribution to the text.